Effect of Process Parameters on Grafting Ratio and Thermal Stability of Lactide-Grafted Sisal Fiber - Chaolin Ye; Guozhen Ma; Zhihua Zhu; Wuchang Fu; Junpeng Duan; Hongwu Wu (Journal of Natural Fibers, 2017)
Polylactide (PLA) was grafted onto sisal fiber (SF) on the basis of the principle of lactide coordinative ring-opening polymerization. The orthogonal test was done to investigate which process parameter affected the grafting ratio mostly. Then the thermal stability of lactide-grafted sisal fiber (SF-g-LA) was studied. Results demonstrated that the lactide was grafted on sisal fiber surface and initiator amount was found to be the most important determinant of the grafting ratio. After grafting copolymerization reaction, the thermal stability of sisal fiber decreased. The increase of grafting ratio does not decreased the thermal stability of SF-g-LA.